Utilization of Google Form as An Evaluation Tool in Islamic Religious Education Learning - Andy Rizki Pratama; Wilda Irsyad; Rahmad Hidayat Hassan (KIPS Institute, 2025)
This research aims to discuss using Google Form as a learning evaluation tool for Islamic Religious Education at Bukittinggi Private Vocational School for the 2023/2024 academic year in class XI majoring in MPLB (Office Management and Business Services). This research includes steps in using Google Forms, from creating the form to analyzing student responses. The advantages and disadvantages of Google Forms as an evaluation tool are discussed in depth. At the same time, the results and discussion include stages of use, student responses, and analysis of evaluation data. This article provides a comprehensive overview of the application of Google Forms in increasing the effectiveness of PAI learning evaluation at Bukittinggi Private Vocational School. The method used in this research is qualitative with a descriptive approach. Data collection techniques were used in the form of observation, interviews, and documentation from the research subjects, namely students of the Bukittinggi Private Vocational School, class XI MPLB. This research shows that Google Form is an effective and efficient solution as a learning evaluation tool for Islamic Religious Education (PAI) subjects at Pembina Bangsa Bukittinggi Vocational School.